Insulinoma-Associated Protein 1 (INSM1) Expression in Neuroendocrine Neoplasms: A Newly Discovered Diagnostic Marker - Sangita A. Vanik; Dhaval Jetly; Karthik Dhandapani (Indian Journal of Medical and Paediatric Oncology)
Introduction Neuroendocrine neoplasms (NENs) are heterogeneous group of neoplasms with relatively low incidence. Diagnosis of NENs requires an integrated approach of histology, immunohistochemistry, and molecular study. In the present study, we evaluated insulinoma-associated protein 1 (INSM1) expression in NENs and correlated it with other established neuroendocrine markers.